Does the Local Application of Platelet-Rich Plasma Reduce Hemorrhage after Tonsillectomy? A Comparative Study - Rasheed, Ahmed M. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Tonsillectomy is one of the most common surgical operations in otolaryngology, post-tonsillectomy hemorrhage is a dangerous complication. Several methods have been used to decrease the rate of post-tonsillectomy hemorrhage, one of these methods, which is a relatively recent method, is the local application of platelet-rich plasma (PRP) to the tonsillar beds.Objectives: To evaluate the role of local application of autologous PRP to the tonsillar beds, at the time of tonsillectomy, in post-tonsillectomy hemorrhage.Patients and methods: A prospective comparative study enrolled 64 patients with ages ranging from 6 to 10 years who underwent tonsillectomy with or without adenoidectomy. In each patient, PRP was applied at the time of tonsillectomy to one tonsillar bed (PRP side), while the other side was used as a control side. So, the total sides were 128 (64 PRP and 64 control sides). The patients were followed up for 10 days and the outcome measure was the occurrence of post-tonsillectomy hemorrhage on the PRP side versus the control side. The association between the variables was established using a chi-square test (X2-test).Results: Thirty-eight patients (59.4%) were males, and twenty-six patients (40.6%) were females. Adenotonsillectomy was performed in 35 patients (54.7%), while 29 patients (45.3%) underwent tonsillectomy alone. There was no post-operative hemorrhage from the adenoid beds. Post-tonsillectomy hemorrhage occurred in 1 patient (1.6%) on the PRP side and 3 patients (4.7%) on the control side (P-value=0.31).Conclusions: The local application of autologous PRP to the tonsillar bed only once, at the time of tonsillectomy, is not significantly effective in reducing post-tonsillectomy hemorrhage